Contemporary educational and behavior change strategies improve dietary practices around a match in professional soccer players - Carter, J. L.; Lee, D. J.; Fenner, J. S. J.; Ranchordas, M. K.; Cole, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
The importance of nutrition in optimizing the health and performance of professional soccer players has been well established. Despite published practical recommendations for the dietary requirements for professional soccer players, many players fail to meet these guidelines. Thus, the primary purpose of this study was to assess the impact of targeted nutritional education and behaviour change interventions on dietary intake in professional football players. Twenty players from the professional development phase in an English Premier League club (age: 18.4 ± 1.0 years; body mass: 76.1 ± 6.0 kg; stature: 1.80 ± 0.07 m) were randomly assigned to an "Intervention" (INT) group (n = 10), who received numerous nutritional education and behaviour change interventions, or a "Control" (CON) group (n = 10), who received no nutrition support. Dietary intake was assessed daily throughout the match week (Match Day (MD)-2, MD-1, MD, MD + 1, and MD + 2). Statistical analyses on the intervention effects on dietary intake were carried out using a two factor (group and day) analysis of variance (ANOVA). Mean energy (3393 ± 852 vs. 2572 ± 577 kcal · day-1) and CHO (5.36 ± 1.9 vs. 3.47 ± 1.1 g · kg-1 BW · day-1) intake were higher (p < 0.001) in the INT vs. CON group. Furthermore, the INT group implemented nutrition periodization practices as CHO intake was increased on MD-1 (7.0 ± 1.7 g · kg-1 BM · day-1), MD (7.1 ± 1.4 g · kg-1 BM · day-1) and MD + 1 (5.1 ± 0.8 g · kg-1 BM · day-1). However, the CON group did not periodize their CHO intake and failed to meet the CHO recommendations on MD-1, MD, and MD + 1 (< 4 g · kg-1 BM · day-1). The implementation of targeted nutritional education and behaviour change interventions resulted in improved dietary practices in professional football players and enabled better adherence to recommended guidelines.